Tafsir Basis Surat Perspective Abdul Hamid Al-Farahi: A Study Of The Concept Of Nazm And Its Application In The Interpretation Of Surah Al-Mursalat - Iskandar Kholis; Zulfikar Azhar; Fadli Ismail (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
Abdul Hamid al-Farahi is one of the Indian Muslim scholars who uses the interpretation of the letter based on the concept of nazm. Surah-based interpretation is interpretation that works on the letter of the Qur'an as a unified whole and has a unified theme (the sura as a unity). In this article, the author tries to explain the concept of nazm initiated by al-Farahi and how this concept is applied in the interpretation of the letter Al-Mursalat. The author uses qualitative research methods with data collection techniques through literature review. This paper shows that al-Farahi's nazm concept is a further development of the munasabah approach. Al-Farahi's concept of nazm emphasizes that each surah has an 'amud surah (central theme). 'Amud functions as a control over the resulting interpretation to build a unified letter. The application of the concept of nazm al-Farahi can be seen from his interpretation of the al-Mursalat letter. Al-Farahi stated that the 'amud of the letter revolves around warnings about the Day of Judgment, obedience to Allah, and doing good among fellow creatures. Thus, every interpretation of the verses in Surah Al-Mursalat must refer to the 'Amud of the Surah.